Tour guide education models - Ćuruvija Ivana; Ćuruvija Miloš (Trendovi u Poslovanju)
Tourism is an intense economic industry, which means significant engagement of employees in the providing of touristic services. Besides, for contemporary, market-oriented touristic business concept, adjustment of touristic services to tourists’ needs and wishes is very important and can be made with high-quality and skilled personnel. In relation to this fact, there is a greater need for specific professions in tourism, including the occupation of professional tour guides. Tour guides represent an important factor of tourism and traveling quality, i.e. the quality of the touristic service. Therefore, it is of the greatest importance that people involved in this occupation be appropriately trained, which can only be made through proper education. The aim of this work is to point out the importance and need for adequate and contemporary tour guide education in Serbia, where tourism was defined as an important economic industry and factor of its development. Likewise, comparing tour guide education in Serbia to the one in certain European countries, in which tourism has reached higher level, led to conclusion of its weaknesses and non-existence of practical training.